2017
DOI: 10.1001/jamaoncol.2016.4983
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Commercially Available Next-Generation Sequencing Platforms in Oncology

Abstract: The growing use of next generation-sequencing to identify cancer-associated alterations as well as the increasing number of targeted drugs holds promise for better matching patients with cancer with effective therapies. The FoundationOne (F1; Foundation Medicine) test sequences clinical tumor samples to characterize the exons of 315 cancer-associated genes and introns from 28 genes involved in rearrangements. The Guardant360 (G360; Guardant Health) test uses cell-free circulating DNA from blood to sequence 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
93
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 6 publications
14
93
0
2
Order By: Relevance
“…This may indicate that variants detected in smaller quantities may only be present in areas that are missed by tissue biopsies and potentially more difficult to detect in blood biopsies. The association of VAF with concordance was also recently reported in a similar comparison between tissue and ctDNA biopsies in a sample of nine patients (43).…”
Section: Discussionsupporting
confidence: 77%
“…This may indicate that variants detected in smaller quantities may only be present in areas that are missed by tissue biopsies and potentially more difficult to detect in blood biopsies. The association of VAF with concordance was also recently reported in a similar comparison between tissue and ctDNA biopsies in a sample of nine patients (43).…”
Section: Discussionsupporting
confidence: 77%
“…Genomic testing of representative tumor biopsies provides mutational status of known driver genes, but methods currently available are reported to be inconsistent (5)(6)(7). Sequential biopsies during therapy have been proposed to capture alterations in driver mutations occurring with selection pressures from systemic therapies (8), which is often contraindicated due to technical or safety issues and patient reluctance.…”
Section: Introductionmentioning
confidence: 99%
“…Mu et al (33 ) showed that 1.3% of the variants detected by NGS were revealed to be false-positives by Sanger sequencing. Other studies also reported discordant NGS results from different laboratories (34,35 ). The errors observed in our study demonstrated that it is essential to have suitable quality control materials to ensure that different assays generate comparable results.…”
Section: Discussionmentioning
confidence: 43%